Analysis of Specific Characteristics of Organizations Providing Higher Education Services - Izzatulla, Levakov (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2023)
This article presents an analysis of the main characteristics of organizations providing higher education services, the most important problems of higher education management.